KORELASI ANTARA MANAJEMEN KELAS DAN MINAT BELAJAR DENGAN HASIL BELAJAR BIOLOGI SISWA - Fadlilah Fadlilah; Arwin Achmad; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
The objective of the research was to know the relationship between class management and learning interest toward the students.  This study design was quantitative description with correlation approach. The samples were the students’ Biology learning result at all SMA at Gadingrejo subdistrict of grade X and XI, chosen by purposive sampling technique. The class management and learning interest data were taken from the questionnaire dan interview, while the learning product data was taken from the block test twice time. The data analysis used simple correlation (Bivariate Pearson) and double correlation. The research result showed that there was a correlation between class management with learning product with the correlation grade 0.639 that was categorized as strong, there was a correlation between learning interest with learning product with the correlation grade 0.724 that was categorized as strong, there was a correlation between class management and learning interest with the learning product with the correlation grade 0.78 that was categorized as strong.  Penelitian ini bertujuan mengetahui hubungan antara manajemen kelas dan minat belajar dengan hasil belajar biologi siswa. Desain penelitian deskriptif kuantitatif dengan pendekatan korelasional. Sampel penelitian siswa SMA se-Kecamatan Gadingrejo kelas X dan XI dipilih secara purposive sampling. Data manajemen kelas dan minat belajar diambil dari angket, dan wawancara, sedangkan data hasil belajar diambil dari tes yang diberikan selama dua kali uji blok. Data dianalisis menggunakan korelasi sederhana (bivariate pearson) dan korelasi ganda. Hasil penelitian menunjukan ada hubungan antara manajemen kelas dengan hasil belajar dengan angka korelasi 0.639 yang berkategori kuat, ada hubungan antara minat belajar dengan hasil belajar dengan angka korelasi 0.724 yang berkategori kuat, ada hubungan antara manajemen kelas dan minat belajar dengan hasil belajar dengan korelasi 0.78 yang berkategori kuat.Kata kunci :  hasil belajar, manajemen kelas, minat belajar